2017
DOI: 10.2174/1874944501710010132
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Plasma Obestatin Levels with BMI and HOMA-IR in Syrian Obese Patients with Type 2 Diabetes

Abstract: Background:Obestatin is a novel hormone derived from preproghrelin, which was reported to inhibit appetite and gastric motility. Study Aim:This study aimed to investigate plasma obestatin levels in obese patients with T2D patients, which had not been studied clearly in last researches. Methods:23 normal weight subjects, 35 obese subjects and 31 obese patients with T2D participated in the study, the body mass index was calculated. Fasting glucose and insulin levels were measured and the homeostasis model assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(23 reference statements)
0
0
1
Order By: Relevance
“…In contrary to our data, Alhalbouni et al, [56] reported that OBST levels were significantly lower in patients with T2DM, and no correlation was found between its level and inflammatory markers in two chronic inflammatory diseases RA and BD.…”
Section: Resultscontrasting
confidence: 99%
“…In contrary to our data, Alhalbouni et al, [56] reported that OBST levels were significantly lower in patients with T2DM, and no correlation was found between its level and inflammatory markers in two chronic inflammatory diseases RA and BD.…”
Section: Resultscontrasting
confidence: 99%